2018
DOI: 10.1103/physrevb.98.115301
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of conduction band plasmons and the related Burstein-Moss shift in highly doped semiconductors: A STEM-EELS study of Ga-doped ZnO

Abstract: The combination of high optical transparency and low electrical resistivity has made transparent conductive oxides (TCOs) a key technology in many optoelectronic applications. Furthermore, the study of TCOs yields insight into many fundamental parameters of semiconductors. For example, the high charge carrier concentration results in an apparent shift in the band gap, the so-called Burstein-Moss shift, in addition to plasmonic resonances in the near infrared regime. While both effects are related to the carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 52 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Specifically, (1) small effective mass m * and (2) large dopant levels n (which are target properties of TCs) increase Δ E g BM , corroborating its presence in n-type TCs but not p-type TCs: However, this equation assumes a single, parabolic band configuration, which indicates the magnitude and intrinsic limits of the BM shift depend on (3) the shape and spacing between bands. Because n-type TCs typically exhibit single-valley and degenerate CBMs, this shift can reach up to 0.5 eV in ITO and Ga-doped ZnO. , In contrast, most p-type TCs exhibit multiple, shallow valence bands (VBs), not a single-valley VBM. These three factors compound in the test set’s p-type TCs such that no noticeable Δ E g BM occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, (1) small effective mass m * and (2) large dopant levels n (which are target properties of TCs) increase Δ E g BM , corroborating its presence in n-type TCs but not p-type TCs: However, this equation assumes a single, parabolic band configuration, which indicates the magnitude and intrinsic limits of the BM shift depend on (3) the shape and spacing between bands. Because n-type TCs typically exhibit single-valley and degenerate CBMs, this shift can reach up to 0.5 eV in ITO and Ga-doped ZnO. , In contrast, most p-type TCs exhibit multiple, shallow valence bands (VBs), not a single-valley VBM. These three factors compound in the test set’s p-type TCs such that no noticeable Δ E g BM occurs.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, the probabilities for change in bandgap for irradiated GZO thin films can be due to; (i) an increase in Zn/O ratio with increasing ion fluence, (ii) activation of Ga dopants sitting at interstitial sites, which contributes to increased carrier concentration, or (iii) formation of defects clusters of Ga Zn -V O . Further, it was reported that in the case of semiconductors, the bandgap increases below Mott's critical concentration and the blue-shift phenomenon in the bandgap is known as Burstein-Moss (BM) effect [43]. Whereas above some critical value of carrier concentration, the narrowing in bandgap was observed and can be understood in the framework of bandgap renormalization (BGN) [44].…”
Section: Optical Propertiesmentioning
confidence: 99%
“…It shows peaks at excitations' frequencies with spectral weights proportional to the rate at which electrons inelastically scatter by corresponding excitations. The method is regularly used to experimentally determine plasmon frequencies in metals [39][40][41], and it is recently applied to study plasmon dispersions in heavily doped semiconductors [42,43]. The EELS measurements should in principle capture phonon-plasmon coupled excitations as well.…”
Section: Introductionmentioning
confidence: 99%